Unveiling the mechanistic nexus: how micronutrient enrichment shapes brain function, and cognitive health - Das, Siddhartha; Banerjee, Pradipta; Jana, Sudipta; Mondal, Hemanshu (Frontiers in Molecular Biosciences, 2025)
Minerals, vitamins, and trace elements are examples of micronutrients essential for psychological wellbeing and brain function. Severe disorders may result from their deficiency or, conversely, from an excess of them. Recent studies have indicated that the etiopathogenesis of certain neurological disorders may involve chronically elevated micronutrient levels. Physiological functions, such as energy metabolism, neurotransmitter synthesis, and antioxidant defence, are regulated by these vital nutrients and are essential for optimal neuronal activity. According to new research, micronutrient enrichment, whether through diet or supplements, can have a significant impact on cognitive function, neuroplasticity, and brain development. Cognitive decline, memory loss, and attention problems are linked to deficiencies in essential micronutrients, including vitamin B12, iron, zinc, and omega-3 fatty acids. Tailored micronutrient therapies have shown promise in reducing age-related cognitive decline and enhancing mental function in both healthy individuals and those at greater risk. This manuscript emphasizes the growing research linking micronutrient status to cognitive health. It also highlights the importance of maintaining a balanced diet and following appropriate supplementation practices to optimize brain function throughout life.